Tierra estabilizada con biopolímeros como una alternativa sostenible para abordar la crisis de la vivienda urbana de bajo costo - Ortega Salinas, Luis Enrique (2024)
The need for a large amount of new housing to cope with rising population and living standards is set against the need to address global warming and declining biodiversity. To overcome this dual challenge, there is an urgent need to evaluate alternative building materials and techniques that are affordable and sustainable. Stabilized earth is a building material that is comparatively cheaper than conventional building materials in low-cost urban housing construction. In addition, building with stabilized earth reduces  emissions and is environmentally sustainable. Despite all the benefits of this material, there are many inhibitors that influence the widespread adoption of earth construction, and prevent this technology from being universally accepted. In this context, this research aims to broaden the understanding of the advantages of earth construction in meeting the growing housing needs and discusses how natural polymers can help change the perception of this material given the potential of these additives to reduce soil permeability, increase strength and improve durability.